Clustering of Ca(2+) transients in interstitial cells of Cajal defines slow wave duration - Drumm, Bernard T. (J Gen Physiol, 2017)
Interstitial cells of Cajal (ICC) in the myenteric plexus region (ICC-MY) of the small intestine are pacemakers that generate rhythmic depolarizations known as slow waves. Slow waves depend on activation of Ca(2+)-activated Cl(−) channels (ANO1) in ICC, propagate actively within networks of ICC-MY, and conduct to smooth muscle cells where they generate action potentials and phasic contractions. Thus, mechanisms of Ca(2+) regulation in ICC are fundamental to the motor patterns of the bowel. Here, we characterize the nature of Ca(2+) transients in ICC-MY within intact muscles, using mice expressing a genetically encoded Ca(2+) sensor, GCaMP3, in ICC. Ca(2+) transients in ICC-MY display a complex firing pattern caused by localized Ca(2+) release events arising from multiple sites in cell somata and processes. Ca(2+) transients are clustered within the time course of slow waves but fire asynchronously during these clusters. The durations of Ca(2+) transient clusters (CTCs) correspond to slow wave durations (plateau phase). Simultaneous imaging and intracellular electrical recordings revealed that the upstroke depolarization of slow waves precedes clusters of Ca(2+) transients. Summation of CTCs results in relatively uniform Ca(2+) responses from one slow wave to another. These Ca(2+) transients are caused by Ca(2+) release from intracellular stores and depend on ryanodine receptors as well as amplification from IP(3) receptors. Reduced extracellular Ca(2+) concentrations and T-type Ca(2+) channel blockers decreased the number of firing sites and firing probability of Ca(2+) transients. In summary, the fundamental electrical events of small intestinal muscles generated by ICC-MY depend on asynchronous firing of Ca(2+) transients from multiple intracellular release sites. These events are organized into clusters by Ca(2+) influx through T-type Ca(2+) channels to sustain activation of ANO1 channels and generate the plateau phase of slow waves.